Obesity-Linked Gut Microbiome Dysbiosis Associated with Derangements in Gut Permeability and Intestinal Cellular Homeostasis Independent of Diet - Ravinder Nagpal; Tiffany M. Newman; Shaohua Wang; Shalini Jain; James F. Lovato; Hariom Yadav (Journal of Diabetes Research)
This study aimed to determine the association between non-high-fat diet-induced obesity- (non-DIO-) associated gut microbiome dysbiosis with gut abnormalities like cellular turnover of intestinal cells, tight junctions, and mucin formation that can impact gut permeability. We used leptin-deficient (Lepob/ob) mice in comparison to C57BL/6J control mice, which are fed on identical diets, and performed comparative and correlative analyses of gut microbiome composition, gut permeability, intestinal structural changes, tight junction-mucin formation, cellular turnover, and stemness genes. We found that obesity impacted cellular turnover of the intestine with increased cell death and cell survival/proliferation gene expression with enhanced stemness, which are associated with increased intestinal permeability, changes in villi/crypt length, and decreased expression of tight junctions and mucus synthesis genes along with dysbiotic gut microbiome signature. Obesity-induced gut microbiome dysbiosis is also associated with abnormal intestinal organoid formation characterized with decreased budding and higher stemness. Results suggest that non-DIO-associated gut microbiome dysbiosis is associated with changes in the intestinal cell death versus cell proliferation homeostasis and functions to control tight junctions and mucous synthesis-regulating gut permeability.